"To support or not to support, that is the question". Testing the VBN theory in predicting support for car use reduction policies in Russia. (January 2019) - Ünal, Ayça Berfu; Steg, Linda; Granskaya, Juliana
Abstract: High use of motorized vehicles is a major cause of CO2 emissions, affecting the quality of the environment negatively. Employing policies that aim to reduce car use would be key to decrease transport-related emissions. However, such policies need to be accepted by the public to be successful. In the current paper, we examine whether support for car use reduction policies can be predicted by the Value-Belief-Norm theory (VBN;Stern, 2000 ), reflecting a process of value triggered norm-activation about reducing one's car use. Notably, we tested the VBN theory in Russia, which is a post-socialist country with a high car use and high transport-related CO2 emissions. As expected, findings indicate that high endorsement of biospheric values is associated with high environmental concern, which is related to an increased awareness of environmental consequences of car use, and a high ascription of responsibility of one's own contribution to environmental problems related to car use. This process leads to strengthening personal norms to reduce own car use, which were associated with higher acceptability of car use reduction policies. The findings indicate that policies that aim at increased support for car use reduction in Russia could target biospheric values and activate personal norms.